CTA Project Completion Report: VALUE4HER - Strengthening women's agribusiness enterprises in Africa - Dido Bashuna, Sabdiyo; Shiri, Mejury; Adedeji, Oluwaseun (Technical Centre for Agricultural and Rural Cooperation, 2020)
CTA developed the programme VALUE4HER, with the aim of increasing value for women in agribusinesses through improved market access and business linkages; improved knowledge, skills, and capacities; and digitally enabled socio and business networking. Adopting three mutually reinforcing approaches, the project embarked on a pathway to increase performance of women agribusinesses and ultimately improve incomes for women agribusinesses leaders.